MENINGKATKAN KEAKTIFAN BELAJAR MURID MELALUI ALAT PERMAINAN EDUKATIF DI KB AN-NUR SUMBERWRINGIN BONDOWOSO - Dwi Febriana, Falisa; M. Fadil Djamali; Eka Olivia Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning activeness is an essential indicator of the quality of early childhood education because it reflects children's physical, cognitive, emotional, and social engagement throughout the learning process. Preliminary observations conducted at KB An-Nur Class B-2, Sumberwringin, Bondowoso revealed that children's learning activeness was relatively low due to the limited availability and poor condition of Educational Play Equipment (EPE), resulting in less varied learning activities and passive classroom participation. This study aimed to improve children's learning activeness through the implementation of cardboard-based Educational Play Equipmentspecifically designed to meet the developmental characteristics of early childhood learners. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, which consisted of two cycles involving the stages of planning, action, observation, and reflection. The research participants were children in Class B-2 of KB An-Nur. Data were collected through structured observations, documentation, and field notes. Learning activeness was assessed using five indicators: participation in learning activities, willingness to ask and answer questions, engagement in using Educational Play Equipment, cooperation with peers, and enthusiasm during classroom activities. The findings demonstrated that the implementation of cardboard-based Educational Play Equipment progressively enhanced children's learning activeness from the initial condition to Cycle I and showed a more substantial improvement in Cycle II after several refinements were introduced, including increasing the number of Educational Play Equipment sets, implementing small-group learning, and providing reinforcement through rewards. These improvements expanded children's opportunities to explore learning media, strengthened social interaction, and encouraged active participation throughout the learning process. The study concludes that cardboard-based Educational Play Equipment is an effective, economical, and environmentally friendly learning medium for enhancing early childhood learning activeness through child-centered, concrete, and enjoyable learning experiences. These findings provide practical implications for early childhood educators in developing innovative learning media from recycled materials to improve the quality of classroom learning